Impact of the fear of Covid-19 infection on intent to breastfeed; a cross sectional survey of a perinatal population in Qatar - Shuja Mohd Reagu; Salwa Abuyaqoub; Isaac Babarinsa; Nisha Abdul Kader; Thomas Farrell; Stephen Lindow; Nahid M. Elhassan; Sami Ouanes; Noor Bawazir; Anum Adnan; Dina Hussain; Malika Boumedjane; et al. (BMC, 2022)
Abstract Objectives Infection control measures during the Covid-19 pandemic have focused on limiting physical contact and decontamination by observing cleaning and hygiene rituals. Breastfeeding requires close physical contact and observance of hygienic measures like handwashing. Worries around contamination increase during the perinatal period and can be expressed as increase in obsessive compulsive symptoms. These symptoms have shown to impact breastfeeding rates. This study attempts to explore any relationship between the Covid-19 pandemic and perinatal obsessive-compulsive symptomatology and whether the Covid-19 pandemic has any impact on intent to breastfeed. Methods A cross sectional survey of perinatal women attending largest maternity centre in Qatar was carried out during the months of October to December 2020. Socio-demographic information, intent to breastfeed and information around obsessive compulsive thoughts around Covid-19 pandemic were collected using validated tools. Results 15.7% respondents report intent to not breastfeed. 21.4% respondents reported obsessive-compulsive symptoms. 77.3% respondents believed the biggest source of infection was from others while as only 12% of the respondents believed that the source of infection was through breastfeeding and 15.7% believed the vertical transmission as the main source of risk of transmission. Conclusions The rates of Obsessive-compulsive symptoms were increased and the rates of intent to breastfeed were decreased when compared with pre pandemic rates. The obsessive-compulsive symptoms and the intent to not breastfeed were significantly associated with fear of infection to the new-born. Obsessive-compulsive symptoms were not significantly correlated with intent to breastfeed and can be seen as adaptive strategies utilized by women to continue breastfeeding in the context of fear of infection.